Moving perforation of rocks using long pulse Nd:YAG laser - Erfan, M.; Shahriar, K.; Sharifzadeh, Mostafa; Ahmadi, M.; Torkamany, M. (2017)
© 2017Laser perforating is a new method in oil and gas wells where researchers look for an alternative to explosive methods. One of the important problems with this method is the generation of uniform and cylindrical holes at a selected pitch for enhancing the permeability of rocks. In non-moving laser perforation, the nozzle of the laser and the rock do not approach each other and due to laser convergence in a point, uniform and cylindrical holes are not created. For this reason, moving laser perforation is suggested in this research. One of the important parameters in moving laser perforation is the power of the laser that can be perforated at a specific rate. In this article we predicted the laser power for a definite rate of perforation (ROP) and then the accuracy of this prediction was evaluated to support the experiments. A pulsed Nd: YAG laser, with a pulse energy around 5.5 J, pulse repetition rate of 30 Hz and pulse duration of 2 ms were used for rock perforation in this study. The results shows that the presented relation for perforation could reliably be used in practice. Furthermore, by knowing the rate of perforation, the required laser power for consistent drilling could be calculated.